Lights, Camera, Nutrition! Can Videos Improve Dietary Knowledge for Future Brides & Grooms? - Zahra Syifa Nurhaliza Mutiara; Fitrianingsih, Asti Dewi Rahayu; Prameswari, Fajria Saliha Puspita; Fauza, Ahdiyatul (LP2M INSURI Ponorogo, 2025)
Preconception nutritional preparedness is crucial to support a healthy pregnancy and prevent fetal growth disorders. In Indonesia, many prospective couples lack adequate understanding of this, making audiovisual-based nutrition education a promising approach; however, its effectiveness still requires further evaluation. This community service aimed to improve nutritional knowledge of prospective brides and grooms through a Communication, Information, and Education (CIE) approach using audiovisual media. The intervention was conducted at the Office of Religious Affairs (KUA) in Sukajadi Subdistrict, Bandung City, involving 74 prospective couples selected through accidental sampling. A 9-minute video containing information on nutritional needs, preconception issues, and recommended intake served as the educational tool. Evaluation used a one-group pretest–posttest design with a validated and reliable questionnaire. The analysis showed a significant increase in knowledge scores after the intervention (N-Gain = 0.44; moderate category). These results suggest that audiovisual-based CIE effectively enhances understanding of preconception nutrition in an engaging and accessible manner. However, the lack of a control group limits the interpretation of the findings. This activity supports audiovisual media as an alternative strategy for preconception nutrition education to enhance readiness for marriage and pregnancy.